If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n in (-oo:+oo)
4-(n/6) = 3 // - 3
4-(n/6)-3 = 0
1-1/6*n = 0 // - 1
-1/6*n = -1 // : -1/6
n = -1/(-1/6)
n = 6
n = 6
| 1/2x-4=14 | | 9r-2s-3rt+7s= | | (2x^2y)(-3x^2y^3)=0 | | (2x^2y)(-3x^2y^3)= | | 2q=-10+4q | | 7b+3a+5-7-2b= | | w=1/2l | | -7-7v=3v+84 | | 120x^2+5x=0 | | 5-4+7x+1=9x+9 | | -41/x−17/x=-39 | | [(4-8)x2-10]/2 | | -66-5n=6+7n | | .4(3x-20)+.6=x+3.8 | | 5-4+7x+1=0x+1 | | 22x+23= | | -39/x−26/x=-46 | | -4x+x-1=0 | | 2x+(3x+50)=180 | | -7-7v=3v+48 | | 9j=-8+10j | | -4=7x+8 | | 5/6=x/14 | | 17x-x^2-60=0 | | 4z+4=9z-28 | | 7b-70-9b=0 | | 15x+5=26x-6 | | 12x=6x+3 | | -7+9h=8h | | -62=7x+8 | | 3w+7=4w+13 | | 5x/3=11 |